A Study of Balinese Traditional Houses through Lontar as a Guideline to Sustainable Design - Wina Satria, Made (KnE Social Sciences, 2019)
Traditional houses usually reflect their surroundings. As they lived among natures, people of the past used resources they found around to build their houses, such as bamboo, reeds, and wood, which is now, remain as traditional housing. The material selections and construction techniques are based on the local environment, social structure, and economic circumstances. This living ways has been going on for a long time and proven to bring positive impacts on the surrounding environment. In Balinese architecture, the proper usage of these resources has been written in lontar manuscripts which are considered as guidelines in Balinese architectural and construction. This study used Lontar Asta Kosala-Kosali from the Geria Jlantik Baler which has been translated into Indonesian. The guidelines related to the basic concept, cosmology, material selections, and construction technique were studied using the interpretative criticism to find the deeper understanding in theory behind this guideline and explore the relation of the built environment and its inhabitant. Guidelines regarding basic concept and cosmology were proven to shows their strong relationship to human and nature which similar to the concept ‘ecological’ and ‘environment.’ The use of woods as the main material which was detailed in the guidelines shows an attempt to make the preservation of the rare and high-quality woods as well as building a durable house. This study may help to see which part of the Asta Kosala Kosali lontar still can be used as a guide by today’s architects to create a sustainable design concept.